A Educação Matemática Inclusiva e o software Scratch: percepções de docentes em uma prática formativa - Bernardino, Ana Clara Dias (2022)
In the present research, we seek to answer the research question: “what pedagogical potential can the Scratch software present for Inclusive Mathematics Education from the perspective of teachers who participated in an extension course?”. We aim to “investigate the teachers' perception about the potential of the Scratch software for the teaching and learning process of Mathematics from the perspective of Inclusive Mathematics Education”. We used as theoretical support the cultural-historical theory, the foundations of defectology and references in the field of Inclusive Mathematics Education. The research was carried out with a qualitative approach, whose data were constructed in a course called “Introduction to Scratch software from the perspective of Inclusive Mathematics Education”. This course took place exclusively remotely and had as participants teachers who taught Mathematics and other subjects in public schools in cities located in the south of Minas Gerais, in Early Childhood Education, Elementary School and High School. The data constitution instruments included recordings (audio and image) of the classes by videoconference, Written Records, Oral Records, Questionnaire, Semi-structured Interview and the researcher's Field Diary. Data were analyzed using the Content Analysis methodology. Two categories of analysis were listed: (1) the potential of the Scratch software in the teaching and learning process of Mathematics from an inclusive perspective; (2) aspects of teacher training and practice in Inclusive Mathematics Education using Scratch. The data indicated teachers' perceptions about the potential of Scratch for teaching Mathematics from an inclusive perspective and about the challenges for using this software in the classroom.